Implant and patient survival rates using Exeter Trauma Stem hemiarthroplasty in fracture neck of femur patients: The largest study to date. Issue 6 (June 2022) - Hammouche, Salah A.; Phillips, Jonathan; Massoumi, Abaris; Scammell, Brigitte E.; Moran, Chris G.
Highlights: Exeter trauma stems have a low implant failure rate when used in fracture neck of femur patients. The design differences between the exeter trauma stems and exeter THR stems did not affect the implant survival rates in NOF patients. Exeter trauma stems implanted in appropriate fracture neck of femur patients are likely to last these patients their whole life. Abstract: Introduction: Exeter Trauma Stems (ETS) femoral hemiarthroplasties are based on Exeter THR stems with a few design changes. Little has been published on ETS survival rates to justify their high cost compared to other cheaper implants. This is the largest prospective study to assess ETS implant failure-free survival rates in fracture neck of femur patients (NOF). This non-developing-centre study examined whether these design differences have altered implant survival (compared with Exeter THR's published survival data). Methods: Data were prospectively collected by independent audit officers. Dislocation, periprosthetic fracture, re-admission with severe hip pain, deep infection and revision surgery were considered events of interest in implant failure-free survival. Results: This study assessed 1, 123 ETS stems (36 patients received bilateral ETS) in NOF patients. The mean patient age at the time of operation was 83 years (range; 49 – 102 years). The mean observation period was 2.5 years (range; 0 days - 8 years). Only 29 implants failed. All failure events were reported within the first year. Stem failure-free survival was 97.2% at eight years (CI 95.9% - 98%). Dislocation occurred in 10 patients (1%), periprosthetic femoral fracture in 4 (0.4%), and deep infection in 11 patients (1.2%). Patient survival rates were 75% and 48% at one and five years respectively. Conclusion: ETS has high implant failure-free survival rates when used in hip fractures. ETS design changes have not altered ETS survival when used in hip fractures compared with the published literature of Exeter THR stem when used as a treatment for OA. Exeter Trauma Stems in NOF patients might last these elderly patients their entire short lifetime.